Hertz Global Holdings (B) : uses of debt and equity 2020 - Rosenthal, Jean, active 2020; Rouwenhorst, K. Geert; Thomas, Jacob; Xu, Allen (London : Yale School of Management, 2021)
In 2019, Hertz held a successful rights offering and restructured some of its debt. CEO Kathyrn Marinello and CFO Jamere Jackson were moving the company toward what seemed to be sustainable profitability, having implemented major structural and financial reforms. Analysts predicted a rosy future. Travel, particularly corporate travel, was increasing as the economy grew. However, positive forecast trajectories turned abruptly with the COVID-19 pandemic. Car rental bookings and revenues plunged as travel, especially business travel, ground to a halt in the first quarter of 2020. Hertz's revenues plummeted and the company found it could not meet its debt payments. In response, Hertz sought protection from its creditors, filing for bankruptcy under Chapter 11.7. The case invites students to consider what options were left open to Hertz as revenues dried up and debt payments came due.
Originally Published InRosenthal, J., Rouwenhorst, G., Thomas, J., & Xu, A. (2021). Hertz Global Holdings (B): Uses of Debt and Equity 2020. 20-031. New Haven, CT: Yale School of Management, Yale University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Business failures -- Case studies; Automobile leasing and renting -- Accounting -- Case studies; Bankruptcy -- Case studies